Machado de Assis, um leitor da Bíblia: uma análise do mito do duplo em Esaú e Jacó - Silva, Glenda da (2015)
This research aims the analysis of the book Esaú e Jacó, written by Machado de Assis, in order to demonstrate the intertextual dialogue between the book and the biblical narrative of the twins Esau and Jacob, recorded in the book of Genesis. Despite the novel not be a work of religious nature, the book s plot. The research divided into three stages that guide this work: First, The Bible and the Literature, we will make recapture o leading scholars and theologians who consider sacred text as literature and as reference source or western narratives. Second, designation: Machado de Assis and the Bible reading: Reverence to the Rebellion, emphasizes two faces the Machado so much both the reverent dialogue and paraphrase until intertextuality the rebel averse. The third chapter entitled: The double myth and Bible in Machado de Assis, analysis the novel, pointing the to double mith presence in Machado s narrative.